2014
DOI: 10.3109/13880209.2014.890230
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antidiabetic properties of cactus pear seed oil in rats

Abstract: Context: Cactus pear (Opuntia ficus-indica (L.) Mill. (Cactaceae)) is a medicinal plant widely used to treat diabetes. Objective: This work investigates the hypoglycemic and antihyperglycemic effect of cactus pear seed oil (CPSO), its mechanism of action, and any toxic effects. Materials and methods: The hypoglycemic effect of CPSO was evaluated in groups of six healthy Wistar rats given 1 or 2 ml kg À1 orally and compared with groups receiving glibenclamide (2 mg kg À1 ) or water. Glycemia was determined afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 32 publications
2
29
0
1
Order By: Relevance
“…seeds, contains high amounts of PUFAs and antioxidant compounds that can be useful in DM management [12][13][14][15][16]. In a previous work, we demonstrated that CPSO improves postprandial hyperglycemia in normal and streptozotocin-induced DM in rats by a partial inhibition of the intestinal glucose absorption [17]. Though, there is no study reporting preventive effect of CPSO against alloxan (Allx) induced-diabetes in mice.…”
Section: Introductionmentioning
confidence: 96%
“…seeds, contains high amounts of PUFAs and antioxidant compounds that can be useful in DM management [12][13][14][15][16]. In a previous work, we demonstrated that CPSO improves postprandial hyperglycemia in normal and streptozotocin-induced DM in rats by a partial inhibition of the intestinal glucose absorption [17]. Though, there is no study reporting preventive effect of CPSO against alloxan (Allx) induced-diabetes in mice.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, the oil from seeds can be potentially used by the food industry for the production of natural-based foods [5], with extended shelf-life [6,7]. More specifically, the oil from cactus pear seeds has been reported to have considerable amounts of unsaturated fatty acids [1], and antioxidant [8,9] or antimicrobial activity [10], as well as cardioprotective, anti-thrombotic, anti-inflammatory, anti-arrhythmic, hypolipidemic, and anti-hyperglycemic properties [11,12]. These properties are of interest for the pharmaceutical and food sector.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this study showed that cactus pear seed oil has anti-diabetic properties by reducing the hyperglycemic effect in both normal and STZ-diabetic rats. The fatty acids found in the cactus pear seed oil were able to increase the secretion of the insulin, enhancing the fluidity of the cell membrane and GLUT4 transporter expression, thus enhancing the glucose-induced insulin secretion [122].…”
Section: Anti-inflammation and Anti-diabetic Activitymentioning
confidence: 99%
“…Cactus has been identified to have anti-diabetic properties due to the presence of compounds such as linoleic acid (polyunsaturated fatty acid), oleic acid (monounsaturated fatty acid), vitamins such as tocopherols and vitamin K1, sterols, and carotenoids [122]. A study was conducted to study the effect of cactus pear seed oil on hypoglycemic and antihyperglycemic and also toxic effects of the oil on the diabetic and non-diabetic rats [122]. The rats were fed the seed oil orally and by intraperitoneal administration and there were no mortality, behavioral, or autonomic effects observed at dosages of 1 mL/kg, 3 mL/kg, or 5 mL/kg.…”
Section: Anti-inflammation and Anti-diabetic Activitymentioning
confidence: 99%